Infections in gynecology and obstetrics. Pharmacodynamics of antibiotics in pregnant women. - Gotuzzo Herencia, Eduardo (2015)
The physiological changes that occur during pregnancy, obviously affect the pharmacodynamics of antibiotics. These changes result in complex situations to be studied, for each antibiotic; on one hand the increased intestinal absorption and decreased serum albumin, produce an increase in the concentration of antibiotic in blood and, secondly, most kidney glomerular filtration and the increased blood volume decreases.